Stable and Fast Lithium–Sulfur Battery Achieved by Rational Design of Multifunctional Separator - Song, Chengwei; Peng, Chengxin; Bian, Zihao; Dong, Fei; Xu, Hongyi; Yang, Junhe; Zheng, Shiyou (Energy & environmental materials (Hoboken, N.J.), 2019)
Lithium–sulfur (Li‐S) battery is considered as one of the most promising candidates for future portable electronics and electric vehicles due to high energy density and potentially low cost. However, the severe polysulfides shuttling in Li‐S battery always causes low Coulombic efficiency, capacity fading, and hindering its practical commercialization. Herein, a dual‐functional PEI@MWCNTs‐CB/MWCNTs/PP (briefly denoted as PMS) separator is assembled through Langmuir–Blodgett–Scooping (LBS) technique for improvement of Li‐S battery performance, that is, rational integrating conductive MWCNTs multilayer on a routine PP separator with polyethyleneimine (PEI) polymer. Owing to “proton‐sponge”‐based PEI feature with the abundant amino/imine groups and branched structures, the PMS separator can provide strong affinity to immobilize the negatively charged polysulfides via electrostatic interaction. Simultaneously, incorporated with the conductive MWCNTs multilayers for the electron transportation, the Li‐S cells assembled with PMS separators achieve exceptional high delivery capacity, good rate performance (~550 mAh g−1 at a current density of 9 A g−1), and stable cycling retention (retention of 84.5% at a current density of 1 A g−1) even over 120 cycles, especially in the case of high‐loading sulfur cathode (80 wt% of S content). This multifunctional separator with dual‐structural architectures via self‐assembly LBS method paves new avenues to develop high‐performance Li‐S batteries. The PEI@MWCNTs‐CB/MWCNTs/PP (PMS) separator retards polysulfides shuttling via chemisorption and physisorption. And, it achieves an extraordinary rate performance and cycling retention, which paves a new avenue to develop high‐performance Li‐S batteries.